Concise Review: Genetic and Epigenetic Regulation of Cardiac Differentiation from Human Pluripotent Stem Cells. (14th May 2019) - Fujita, Jun; Tohyama, Shugo; Kishino, Yoshikazu; Okada, Marina; Morita, Yuika
Abstract: Human pluripotent stem cells (hPSCs), including both embryonic stem cells and induced pluripotent stem cells, are the ideal cell sources for disease modeling, drug discovery, and regenerative medicine. In particular, regenerative therapy with hPSC-derived cardiomyocytes (CMs) is an unmet medical need for the treatment of severe heart failure. Cardiac differentiation protocols from hPSCs are made on the basis of cardiac development in vivo. However, current protocols have yet to yield 100% pure CMs, and their maturity is low. Cardiac development is regulated by the cardiac gene network, including transcription factors (TFs). According to our current understanding of cardiac development, cardiac TFs are sequentially expressed during cardiac commitment in hPSCs. Expression levels of each gene are strictly regulated by epigenetic modifications. DNA methylation, histone modification, and noncoding RNAs significantly influence cardiac differentiation. These complex circuits of genetic and epigenetic factors dynamically affect protein expression and metabolic changes in cardiac differentiation and maturation. Here, we review cardiac differentiation protocols and their molecular machinery, closing with a discussion of the future challenges for producing hPSC-derived CMs. Stem Cells   2019;37:992–1002 : Abstract :